2018
DOI: 10.1042/cs20171606
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) reduces cardiac effects of thyroid hormone by GSK3Β/NFATc3 signaling pathway

Abstract: Patients with hyperthyroidism exhibit increased risk of development and progression of cardiac diseases. The activation of the renin-angiotensin system (RAS) has been indirectly implicated in these cardiac effects observed in hyperthyroidism. Angiotensin-(1-7) (Ang-(1-7)) has previously been shown to counterbalance pathological effects of angiotensin II (Ang II). The aim of the present study was to investigate the effects of elevated circulating Ang-(1-7) levels on cardiac effects promoted by hyperthyroidism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…Sadoshima and colleagues showed the presence of intracellular vesicles in cardiomyocytes containing AngII that could be secreted under mechanical stretch (Sadoshima et al, 1993). Previous data of our group reported the increased expression of AngI/II in cardiac cells treated by TH-in vivo and in vitro-and the increased concentration of this peptide in the culture medium of cardiomyocytes (Diniz et al, 2009;Senger et al, 2018). However,…”
Section: Discussionmentioning
confidence: 88%
“…Sadoshima and colleagues showed the presence of intracellular vesicles in cardiomyocytes containing AngII that could be secreted under mechanical stretch (Sadoshima et al, 1993). Previous data of our group reported the increased expression of AngI/II in cardiac cells treated by TH-in vivo and in vitro-and the increased concentration of this peptide in the culture medium of cardiomyocytes (Diniz et al, 2009;Senger et al, 2018). However,…”
Section: Discussionmentioning
confidence: 88%
“…In the hyperthyroid state, an upregulation of Ang-(1-7), ACE2 activity and the MAS receptor in the heart was demonstrated, with no changes in the plasma levels of Ang-(1-7) (123). Contributing to these data, recently it was shown that elevated circulating levels of Ang-(1-7) prevented T3-induced cardiac hypertrophy by attenuating the glycogen synthase kinase 3 beta/nuclear factor of activated T-cells (GSK3β/NFATc3) signaling pathway (124) (Fig. 2).…”
Section: Interaction Of Th With Other Endocrine Systemsmentioning
confidence: 80%
“…Thyroid hormones cause the activation of intracellular PI3K-Akt/Gsk3β and Mapk signaling pathways by interacting with the specialized membrane proteins monocarboxylate transporter 8 and integrin αVβ3, which are involved in the communication between the extracellular and intracellular environment, with their non-genomic effect. The non-genomic effects of thyroid hormones are short term [1][2][3][4] . The main effect of thyroid hormone is genomic, it binds to its receptors in the nucleus and initiates various transcription events and directly affects the biological functions of the cell 1 .…”
Section: Introductionmentioning
confidence: 99%